Study of decay properties of D and Ds mesons. (30th August 2016) - Yazarloo, B. H.; Mehraban, H.
Abstract: We present a theoretical approach to obtain the decay properties of D and D s mesons. As the Cornell potential includes confinement because of the linear potential, and it also includes the single-gluon exchange potential, which is the Coulomb potential, we have considered this potential for the study of mesonic systems. The two-parameter variational method has been applied to investigate the masses and the decay properties of mesons. It has been observed that the predictions of the masses and decay widths are consistent with other model predictions as well as with the known experimental values.